Revelation 19.16's Inscribed Thigh: An Allusion to Gen 49.10b - Lear, Sheree (New Testament studies, 2014)
The inscribed thigh of the rider on the white horse in Rev 19.16 is an allusion to an MT - like Gen 49.10b text. The phrase ‘inscribed on his thigh’ was a legitimate translation of the words found in Gen 49.10b at the time of the composition of Revelation.